FAKTOR-FAKTOR KEPUASAN PENGGUNA TERHADAP KUALITAS PELAYANAN DI TERMINAL MENGWI BADUNG - SEPTYADI, ZANUAR; SRINADI, I GUSTI AYU MADE; JAYANEGARA, KETUT (E-Jurnal Matematika; Vol 9 No 2 (2020), 2020)
Customer satisfaction is the level of customer feeling towards the evaluation of perceived discrepancies between performance or perceived results compared to expectations. Quality is the level of excellence expected to meet customer desires which is a dynamic condition related to products, services, people, processes and the environment that meets or exceeds expectations. Factor analysis is a multivariate analysis method based on correlations between variables. This study discusses the factors of customer satisfaction with service quality in the Mengwi Badung Station. The factors of user satisfaction with the quality of service at the Mengwi Badung Station are caring, physical condition, guarantee, reliability, and responsibility factors.